Confocal laser scanning microscopic evaluation of sealing ability of bone cement, mineral trioxide aggregate and biodentine as root-end filling materials: An in vitro study - Shalin Ann Saji; Tony Mathew; Aditya Shetty; Gurmeen Kaur; Sunheri Bajpe (Wolters Kluwer Medknow Publications, 2022)
Aim: To compare the sealing ability of polymethylmethacrylate (PMMA) bone cement, mineral trioxide aggregate (MTA), and Biodentine as root-end filling materials by assessing the degree of microleakage through confocal laser scanning microscopy. Materials and Methods: Thirty extracted maxillary incisors were root canal treated using the rotary ProTaper system. Apical root resections followed by retrograde cavity preparation were done. The teeth were divided into three groups and filled with the 3 tested materials (PMMA bone cement, MTA, and Biodentine). Samples were coated with nail varnish, immersed in 0.5% aqueous solution of rhodamine B dye for 24 h, and rinsed with water to remove excess dye. Samples were horizontally sectioned at 1 mm intervals into three using a diamond disk and were labeled A, B, and C and considered first, second, and third, respectively, based on their distance from the apex. Each slice was divided into four equal parts and evaluated using a confocal laser scanning microscope. Dye penetration was scored based on the amount of microleakage. The data were analyzed using one-way analysis of variance. Results: Intergroup comparison of the mean scores of dye penetration among the three materials showed that there is a statistical difference between PMMA bone cement, MTA, and Biodentine, in sections B and C (P ≤ 0.05). The three groups showed no statistical difference in dye penetration scores in section A. Conclusion: The microleakage is least with PMMA bone cement followed by Biodentine and MTA. Microleakage was least in section C followed by sections B and A.